1996
DOI: 10.1097/00005392-199608001-00022
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Small Functional Bladder Capacity and and Other Predictors on the Response to Desmopressin in the Management of Monosymptomatic Nocturnal Enuresis

Abstract: The responsiveness of children with nocturnal enuresis to desmopressin is adversely affected by reduced functional bladder capacity. The results of this study have implications regarding the potential use of combination pharmacotherapy with desmopressin and an anticholinergic for enuretic patients who are nonresponsive to single drug therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
0
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 24 publications
3
47
0
1
Order By: Relevance
“…With regard to the significance of urinary osmolality testing, Rushton et al [6], in a separate study, revealed similar results to ours when evaluating the predictive value of spot urinary osmolalities. The urine collections were, however, at slightly different times (06:00 and 18:00) but were also performed in the ambulatory setting.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…With regard to the significance of urinary osmolality testing, Rushton et al [6], in a separate study, revealed similar results to ours when evaluating the predictive value of spot urinary osmolalities. The urine collections were, however, at slightly different times (06:00 and 18:00) but were also performed in the ambulatory setting.…”
Section: Discussionsupporting
confidence: 86%
“…In a recent publication, Rushton et al [6] studied possible predictive factors of response to DDAVP therapy and conclude that response to DDAVP was adversely affected by a reduced functional bladder capacity. This is consistent with our study which revealed that bladder capacity as a percentage of normal was the variable with the highest predictive value in the statistical model.…”
Section: Discussionmentioning
confidence: 99%
“…Eller et al [9], Rushton et al [13]and Folwell et al [14]described that children with nocturnal enuresis who manifested a reduced bladder capacity during the day were found to be less likely to respond to DDAVP. The data obtained in the present study are in agreement with their experience.…”
Section: Discussionmentioning
confidence: 99%
“…The data obtained in the present study are in agreement with their experience. Further, Eller et al [9]and Rushton et al [13], found that spot urine osmolalities in the early morning were not predictive of a response to DDAVP (p>0.1). In our experience, there were observable variations between days in first morning urine osmolalities of the same patients.…”
Section: Discussionmentioning
confidence: 99%
“…Since detrusor overactivity implies that the detrusor is not perfectly relaxed between voidings, the reservoir capacity of the overactive bladder will be smaller than in a bladder with a normally relaxed detrusor. And recently, several studies have reported that many enuretics without daytime symptoms seem to have reduced bladder capacity [15, 16, 17]. These new facts that as many as one third of the enuretic population may have a reduced reservoir capacity, at least during sleep, bear important clinical consequences for the clinical management.…”
Section: Pathophysiologymentioning
confidence: 99%